Hedonic Browsing Behaviour and Its Impact on Impulsive Buying Among Generation Z - Deandra Vidyanata; Yopy Junianto; Auditia Setiobudi (LPPM Universitas Buddhi Dharma, 2024)
This research investigates the changing dynamics of digital consumer behavior, specifically examining how Generation Z's participation in hedonic browsing activities influences their tendency towards impulsive online purchasing. This study employs a purposive sampling method, targeting Generation Z individuals who have recently made online purchases. A total of 195 respondents were surveyed, using a structured questionnaire to assess their hedonic browsing behavior, positive emotional responses, and tendencies towards impulsive buying. The findings reveal a strong statistical significance in the relationship between hedonic browsing behavior and impulsive buying behavior. Hedonic behavior, characterized by leisurely and pleasure-seeking online activities, significantly increases the likelihood of impulsive purchases. Furthermore, the study highlights the crucial mediating role of positive emotions in this relationship, indicating that the emotional states elicited by hedonic activities directly influence spontaneous buying decisions.